Developing ICT Services in a Low-Resource Development Context - Bon, Anna; Akkermans, Hans; Gordijn, Jaap (Complex Systems Informatics and Modeling Quarterly, 2016)
Despite an urgent need for social and technological innovation to improve wellbeing of people and communities in poor regions of the world, information and communications technology (ICT) service delivery has not yet been very successful in regions with low levels of literacy, poor infrastructures, and limited purchasing power. High rates of failure, reported in various studies, point at a frequent mismatch between deployed technologies and local needs and contexts. Still, no practical field-validated methodologies for ICT service innovation in low-resource development contexts have been proposed that offer adequate ways to meet local needs and contexts and assess sustainability before deployment. This article outlines a framework for development of ICT services in low-resource development contexts, covering the full lifecycle of ICT service innovation. This framework is based on extensive field research, and shows how a collaborative, adaptive, and iterative methodology can address a set of key sociotechnical concerns and issues widely encountered in developing and emerging countries.